Changing literacy instruction in Kenyan classrooms: Assessing pathways of influence to improved early literacy outcomes in the HALI intervention. (September 2018) - Wolf, Sharon; Turner, Elizabeth L.; Jukes, Matthew C.H.; Dubeck, Margaret M.
Abstract: This study uses data from the Health and Literacy Intervention (HALI) program evaluation, an in-service teacher training program focused on early grade literacy instruction for class one teachers. We assess how changes in classroom instructional processes impacted by the HALI teacher training were associated with improved early literacy outcomes for children. We find that experimentally induced increases in exposure to print—measured both through changes to time spent reading in class and through print displayed in the classroom—were associated with improvements in students' reading fluency and reading comprehension. Implications for global education efforts to improve learning outcomes are discussed.